The origin of evil - Queen, Ellery (Ellery Queen Detective, 2014)
Knowing a package containing a dead dog would literally frighten its intended victim to death, a cunning enemy delivers this perfect murder weapon to Leander Hill, a prominent Hollywood jeweler.When Hill's daughter enlists the support of Queen, he must harness all of his skills to prevail over this unscrupulous mind.